Utilizing Sentinel-2 Remote Sensing for Water Quality Monitoring in Deran Lake, Bosnia and Herzegovina - A. Batina; A. Šiljeg; G. Pedić; M. Parać (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This study evaluates the effectiveness of Sentinel-2 MSI imagery, corrected using the Case-2 Regional Coast Colour (C2RCC) algorithm in SNAP software (Sentinel Application Platform), for estimating chlorophyll-a (Chl-a) and total suspended solids (TSS) in Deran Lake, a karstic lake with minimal anthropogenic pressure within Hutovo Blato Nature Park, Bosnia and Herzegovina. In situ measurements were collected in March 2025 using a YSI EXO2s multiparameter probe at ten monitoring stations under the SMART-Water project. TSS was used as a proxy for total suspended matter (TSM). A regression analysis between satellite-derived and measured values showed a strong correlation for TSS/TSM (R2 = 0.76) and a moderate correlation for Chl-a (R2 = 0.61). Spatial averaging over 5×5-pixel windows improved estimation accuracy, yielding R2 values of 0.85 for TSS/TSM and 0.69 for Chl-a. Thematics maps of SNAP-derived Chl-a and TSS/TSM distribution was performed using QGIS 3.40. Chl-a concentrations confirmed oligotrophic conditions, while TSS patterns aligned with known hydrodynamic features such as inflow zones and sediment resuspension areas. These findings align with other regional studies demonstrating Sentinel-2’s potential for monitoring small and optically complex waterbodies when paired with appropriate atmospheric correction, statistical estimators (e.g., mean), and spatial windowing strategies. This work reinforces the value of remote sensing for cost-effective, high-resolution monitoring of inland waters, improving water resource management across diverse ecosystems.